2023
DOI: 10.1021/acssuschemeng.3c04115
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Recyclable Photobiocatalytic System via Cofactor Regeneration for Chiral Aryl Alcohol Synthesis

Chun-Xian Cai,
Zi-Wen Zhou,
Chun-Xiu Liu
et al.

Abstract: Integrating efficient enzyme catalysis and sustainable photocatalysis is considered an eco-friendly and promising approach for substance conversion. In this work, employing a highly selective ketoreductase and a metal-free photocatalyst covalent organic framework (COF), we rationally constructed a coimmobilized biocatalyzed artificial photosynthesis system mediated by cofactor regeneration for chiral alcohol synthesis. COFs (denoted as TTA-T 0 and TTA-T 2 ) were rapidly fabricated at a moderate condition for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Chiral alcohols are valuable building blocks used in the synthesis of, particularly, pharmaceuticals, agrochemicals, and fine chemicals and have drawn extensive attention in the field of catalysis. A considerable number of significant active intermediates and top-selling drugs contain chiral alcohol moieties. In the context, ( S )-1-phenylethanol can be employed as a synthetic precursor to prepare sertraline for treating depression, asmalar for treating asthma, and levamisole for enhancing the immune system. ( R )-2-chloro-1-phenylethanol and ( S )-1-(2,6-dichloro-3-fluorophenyl)-ethanol are the intermediates for synthesizing fluoxetine and crizotinib, respectively. , (+)-Bacillamide exhibits anti-HIV activities and lovastatin displays potential for the prevention and treatment of various types of cancers and cholesterolemic and neurological disorders (Figure ). , The classical synthetic procedures of chiral alcohol compounds usually rely on harsh reaction conditions such as high pressure and temperature, expensive chiral ligands, and environmentally unfriendly organic reagents. Therefore, developing efficient, economical, and sustainable routes for chiral alcohol synthesis is urgently needed owing to the rising shortage of resources and environmental concerns. , Various oxidoreductases such as ketoreductases (KREDs), also known as alcohol dehydrogenases (ADHs), have been employed for the asymmetric reduction of ketones to produce chiral alcohols for their merits of excellent enantioselectivity, specificity, and benign conditions. , However, more than 80% of enzymatic reductions from ketones catalyzed by oxidoreductases require a cofactor NAD(P)H as the hydrogen source to be consumed for accomplishing catalytic functions. , In the last decades, extensive efforts have been made toward exploring simple and suitable methods for cofactor regeneration. ,, Despite the significant progress that has been made in the regeneration of NAD(P)H via biocatalytic, electrochemical, and photochemical methods, biocatalysts that do not rely on cofactors for the fabrication of chiral alcohols still remain to be further explored. , Recently, a human carbonic anhydrase II (hCAII) was reported that exhibited excellent catalytic activity and enantioselectivity in the asymmetric reduction of ketones with silanes as the reductant . Further advantages such as a broad substrate scope, mild reaction conditions, and avoidance of cofactor...…”
Section: Introductionmentioning
confidence: 99%
“…Chiral alcohols are valuable building blocks used in the synthesis of, particularly, pharmaceuticals, agrochemicals, and fine chemicals and have drawn extensive attention in the field of catalysis. A considerable number of significant active intermediates and top-selling drugs contain chiral alcohol moieties. In the context, ( S )-1-phenylethanol can be employed as a synthetic precursor to prepare sertraline for treating depression, asmalar for treating asthma, and levamisole for enhancing the immune system. ( R )-2-chloro-1-phenylethanol and ( S )-1-(2,6-dichloro-3-fluorophenyl)-ethanol are the intermediates for synthesizing fluoxetine and crizotinib, respectively. , (+)-Bacillamide exhibits anti-HIV activities and lovastatin displays potential for the prevention and treatment of various types of cancers and cholesterolemic and neurological disorders (Figure ). , The classical synthetic procedures of chiral alcohol compounds usually rely on harsh reaction conditions such as high pressure and temperature, expensive chiral ligands, and environmentally unfriendly organic reagents. Therefore, developing efficient, economical, and sustainable routes for chiral alcohol synthesis is urgently needed owing to the rising shortage of resources and environmental concerns. , Various oxidoreductases such as ketoreductases (KREDs), also known as alcohol dehydrogenases (ADHs), have been employed for the asymmetric reduction of ketones to produce chiral alcohols for their merits of excellent enantioselectivity, specificity, and benign conditions. , However, more than 80% of enzymatic reductions from ketones catalyzed by oxidoreductases require a cofactor NAD(P)H as the hydrogen source to be consumed for accomplishing catalytic functions. , In the last decades, extensive efforts have been made toward exploring simple and suitable methods for cofactor regeneration. ,, Despite the significant progress that has been made in the regeneration of NAD(P)H via biocatalytic, electrochemical, and photochemical methods, biocatalysts that do not rely on cofactors for the fabrication of chiral alcohols still remain to be further explored. , Recently, a human carbonic anhydrase II (hCAII) was reported that exhibited excellent catalytic activity and enantioselectivity in the asymmetric reduction of ketones with silanes as the reductant . Further advantages such as a broad substrate scope, mild reaction conditions, and avoidance of cofactor...…”
Section: Introductionmentioning
confidence: 99%